Xưng hô bằng danh từ chỉ chức vụ, nghề nghiệp trong tiếng Hàn (Có liên hệ với tiếng Việt)./Lã Thị Thanh Mai. - Lã Thị Thanh Mai.
In this research, we indicate 5 typical means of addressing people by job title and occupation in Korean language in accordance with their honorific level. Besides, we also introduce some other addressing ways by educational degree and social rank, which are widely used in Korean society. Finally, we give a list of addressing nouns of job title and occupation combined with the suffix 님/ nim normally indicating respect. It can be seen that addressing by job title and occupation is more popularly used in Korean languages than in Vietnamese language. These expressions are frequently used in working places in Korea.